Peran Badan Penanggulangan Bencana Daerah Dalam Mengatasi Kekeringan Di Kabupaten Wonogiri - Krismona Dewi Arini; Asianto Nugroho (Jurnal Discretie, 2020)
The purpose of this study was to determine the implementation of disaster management in Wonogiri Regency, as well as the technical and non-technical obstacles it faces. This research is a normative study with a statutory approach. The results showed that, the urgency of implementing drought disaster management in Wonogiri Regency based on the Regional Regulation of Wonogiri Regency Article 37 (2) Number 7 of 2016 through a juridical study is in accordance with vertical synchronization and harmonization of applicable laws and regulations. The Regional Disaster Management Agency of Wonogiri Regency as a disaster management task force through the Regional Budget Fund, in accordance with its authority has implemented disaster management during pre-disaster, emergency response, and post-drought disaster in 2017, 2018, 2019, and until the end. in August 2020 with the assistance of donors in the Wonogiri Regency area and from outside Wonogiri Regency.